Poverty, hunger, and abandonment: representations of the nursing team about homeless persons - Mayara Novais Pereira Zandomingo; Jeane Freitas de Oliveira; Dejeane de Oliveira Silva; Carle Porcino; Cleuma Sueli Santos Suto; Daiane Santos Oliveira (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to know the structure of social representations of nursing team with regard to homeless persons. Method a qualitative research based on the structural approach of social representations. A total of 96 professionals from the nursing team working in the Psychosocial Care Network units of a Health District of Salvador, Bahia, Brazil, who answered the test of free association of words and a questionnaire with socio-demographic data. The data obtained were processed in softwares that allowed the organization of the frame of four houses and maximum similarity tree. Results: poverty, hunger, abandonment and unemployment are central elements of the image of homeless persons, living in a context permeated by drugs, dirt, neglect and vulnerability. Final considerations The social representation structure of homeless persons is anchored in stereotypes that can interfere both in the provision of care and in the access of the people to health services.